Minds, ethics, and conditionals : themes from the philosophy of Frank Jackson - Ravenscroft, Ian. (Oxford : Clarendon Press, 2010)
An international line-up of contributors present new essays on themes from the philosophy of Frank Jackson, discussing his groundbreaking work on supervenience and conceptual analysis mind and colour; normative ethics and metaethics; and conditionals. Jackson offers a substantial reply to his critics.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Jackson, Frank, -- 1943- -- Themes, motives; Metaphysics; Philosophy of mind; Conditionals (Logic); Consequentialism (Ethics)